Pricing Currency Risk: Facts and Puzzles from Currency Boards - Schmukler, Sergio L.; Servén, Luis (World Bank, Washington, D.C., 2013)
The authors investigate the patterns and determinants of the currency risk premium in two currency boards-Argentina and Hong Kong. Despite the presumed rigidity of currency boards, currency premium is almost always positive and at times very large. Its term structure is usually upward sloping, but flattens out or even becomes inverted at times of turbulence. Currency premia differ across markets. The forward discount typically exceeds the currency premium derived from interbank rates, particularly during times of crisis. The large magnitude of these cross-market differences can be the consequence of unexploited arbitrage opportunities, market segmentation, or other risks embedded in typical measures of currency risk. The premium and its term structure depend on domestic and global factors related to devaluation expectations and risk perceptions.